2005
DOI: 10.1056/nejmoa044029
|View full text |Cite
|
Sign up to set email alerts
|

Screening the Blood Supply for West Nile Virus RNA by Nucleic Acid Amplification Testing

Abstract: Although nucleic acid amplification testing of minipools of blood donations prevented hundreds of cases of West Nile virus infection in 2003, it failed to detect units with a low level of viremia, some of which were antibody-negative and infectious. These data support the use of targeted nucleic acid amplification testing of individual donations in high-prevalence regions, a strategy that was implemented successfully in 2004.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(143 citation statements)
references
References 17 publications
(26 reference statements)
2
140
0
1
Order By: Relevance
“…In the United States, national blood donor screening using minipool (MP) nucleic acid testing (NAT) was initiated in 2003. This rapidly implemented screening strategy prevented the release of presumably infectious blood products from more than 500 donors (27,28). Despite the success of screening, retrospective studies showed that MP-NAT missed some low-level viremic donations and thus could not completely eliminate the risk of acquiring infection by transfusion of infected blood products (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, national blood donor screening using minipool (MP) nucleic acid testing (NAT) was initiated in 2003. This rapidly implemented screening strategy prevented the release of presumably infectious blood products from more than 500 donors (27,28). Despite the success of screening, retrospective studies showed that MP-NAT missed some low-level viremic donations and thus could not completely eliminate the risk of acquiring infection by transfusion of infected blood products (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…This rapidly implemented screening strategy prevented the release of presumably infectious blood products from more than 500 donors (27,28). Despite the success of screening, retrospective studies showed that MP-NAT missed some low-level viremic donations and thus could not completely eliminate the risk of acquiring infection by transfusion of infected blood products (27)(28)(29). Therefore, screening strategies were investigated and the switch was made from MP-NAT to individual donor-NAT, which has been shown to be the most sensitive method for detecting viremic donations (30).…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative DENV RNA assay (18,20) uses the same technology as the FDA-licensed Procleix WNV assay (2,11,17,33). Briefly, 500 l of specimen was added to a detergent solution (target capture reagent), and viral RNA was isolated using magnetism-based target capture.…”
Section: Methodsmentioning
confidence: 99%
“…Since its emergence in the United States in 1999, Ϸ26,000 cases of symptomatic WNV infection have been confirmed (www.cdc. gov/ncidod/dvbid/westnile/surv&control.htm#maps), and seroprevalence studies suggest that several million people have been infected (1).…”
Section: W Est Nile Virus (Wnv) Is a Neurotropic Member Of Thementioning
confidence: 99%